CUSTOMIZED PERIODONTICS: A BLUEPRINT FOR ACCURATE PERIODONTAL TREATMENT – A NARRATIVE REVIEW - Dr Sarmatha Selvaraj S; Dr Magesh Kumar S (IJRDO-Journal of Applied Science, 2025)
Personalized periodontics is an emerging paradigm in dental medicine that redefines periodontal care through precision-based strategies. Recognizing that periodontal disease progression and response to therapy vary significantly among individuals, this approach integrates genetic, microbial, immunological, and lifestyle data to deliver tailored diagnostics and treatments. Biomarkers such as IL-1β, MMP-8, and microbial DNA profiles, along with systemic indicators like HbA1c and host-response polymorphisms, enable more refined staging and grading of disease. Therapeutic decisions are increasingly guided by real-time biosensors, AI-driven risk models, and individualized treatment protocols that range from non-invasive interventions in low-risk patients to biologically guided regenerative therapies in complex cases. Digital tools and multi-omics platforms further support dynamic monitoring and decision-making. This paradigm offers enhanced clinical outcomes, improved patient engagement, and more efficient use of healthcare resources. As research evolves, the integration of chairside diagnostics and molecular precision will likely become standard in periodontal care.